PELAKSANAAN KEWAJIBAN KEPALA DESA DALAM MEMBERDAYAKAN MASYARAKAT DAN LEMBAGA KEMASYRAKATAN DESA DI DESA LUBUK BETUNG KECAMATAN ROKAN IV KOTO KABUPATENROKAN HULU TAHUN 2016- 2017 - ", Uniati; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
One village head is empowering local communities and rural public institutions in accordance with the folk song, which is interpreted as governing to meet the needs desired by individuals, organizations and the public. In order to meet the needs of society, the head of the village of Bruno should hand over his duties to the people of Bethan Better. How does the head of the village perform his duties in delegating to the village community and the village on of Lubuk Betung sub distict Rokan IV Koto distircts Rokan Hulu from 2016-2017? When it became a factor in the maintenance of the village on, of Lubuk Betung sub distict Rokan IV Koto distircts Rokan Hulu from 2016-2017 the chief’s duty could be fulfilled. This study is for the explanation of village responsibility and the application of the city’s social responsibility performance in self-regulating the general public and the community, and for the obstrucation of the performance of social responsibility of the local community in the subway system,of Lubuk Betung sub distict Rokan IV Koto distircts Rokan Hulu the following are the secrets of the louclout Cutter: The techniques used in data collection, data analysis performed by qualitative access, interview, and document data analysis were by data recall, data entry,and withdrawal it’s a theory. The results of this study could suggest that the performance of the work is optimally implemented in accommodating the residents of Lubuk Betung sub distict Rokan IV Koto distircts Rokan Hulu village and community whose village maintenance has not yet been completed. Village society, but little definite activity has been realized in the implementation process. It is the element of social return and delegating it to the social and village public institutions of Lubuk Betung sub distict Rokan IV Koto distircts Rokan Hulu has two, internal and external elements.Keywords :Village government,Village Head, community empowerment